A New Clinical Tool for Scoliosis Risk Analysis: Scoliosis Tele-Screening Test - Hurriyet Gursel Yılmaz; Ahsen Büyükaslan; Aslihan Kuşvuran; Zeynep Turan; Filiz Tuna; Hande Tunc; Sibel Özdoğan (Asian Spine Journal, 2023)
Study Design Methodological, observational clinical study. Purpose: This study aimed to develop a virtual screening test to detect scoliosis risk initially by parents without the need for medical visit during the coronavirus disease 2019 pandemic. Overview of Literature The scoliosis screening program has been implemented to early detect scoliosis. Unfortunately, access to health professionals was limited during the pandemic. However, during this time, interest in telemedicine has increased remarkably. Recently, mobile applications related to postural analysis were developed, but none permits evaluation by parents. Methods: Researchers developed the Scoliosis Tele-Screening Test (STS-Test), which included drawing-based images of body asymmetries, to assess the scoliosis-associated risk factors. The STS-Test was shared on social networks, allowing the parents to evaluate their children. After test completion, the risk score was generated automatically, and children with medium and high risks were then advised for medical consultation for further evaluation. The test accuracy and consistency between the clinician and parents were also analyzed. Results: Of the 865 tested children, 358 (41.4%) consulted clinicians to confirm their STS-Test results. Scoliosis was then confirmed in 91 children (25.4%). The parents were able to detect asymmetry in 50% of the lumbar/thoracolumbar curvatures and 82% of the thoracic curvatures. In addition, the forward bend test revealed favorable agreement between parents and clinicians (r=0.809, p<0.0005). Internal consistency of the esthetic deformities domain in the STS-Test was also excellent (α=0.901). This tool was 94.97% accurate, 83.51% sensitive, and 98.87% specific. Conclusions: The STS-Test is a new parent-friendly, virtual, cost-effective, result-oriented, and reliable tool for scoliosis screening. It allows parents to actively participate in the early detection of scoliosis by screening their children for the risk of scoliosis periodically without the need to visit the health institution.